GDP management to meet or beat growth targets - Lyu, Changjiang; Wang, Kemin; Zhang, Frank; Zhang, Xin (Journal of Accounting and Economics, 2018)
We apply the discontinuity methodology from the accounting literature to a political economy setting of GDP reporting and examine whether Chinese local governments manage regional GDP numbers. We find strong evidence of discontinuities around zero in the distribution of actual minus target GDP growth rates. The frequencies of just meeting or beating GDP growth targets are about five (four) times the frequencies of just missing targets at the prefecture (province) level. The results are stronger for governors with longer tenures and those without political connections to higher-level officials as well as for local governments with more resources under their control.